Competitive equilibrium and growth supports in the Von Neumann model - Uribe, Pedro (Estudios Económicos de El Colegio de México, 1991)
This paper shows the existence of a reproducible competitive equilibrium in the general Von Neumann growth model, extending in this way a result due to Roemer.